Naivety about hidden information: An experimental investigation - María Montero Mu\~noz; Jesal D. Sheth (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2019)
The unravelling prediction of disclosure theory relies on the idea that strategic forces lead firms (information senders) to voluntarily disclose information about the quality of their products provided the information disclosed is verifiable and the costs of disclosure are negligible. This theoretical prediction requires that consumers (information receivers) hold correct beliefs about non-disclosed information and, in equilibrium, treat all non-disclosed information with extreme scepticism. Previous research finds that receivers are insufficiently sceptical, or in other words are naive, about non-disclosed information, which leads to the failure of unravelling. This paper examines the extent to which naivety responds systematically to features of the decision environment, namely the availability of opportunities to communicate with others (Consultation treatment) and the context of the experimental setting (Context treatment, based on hygiene ratings). We find that complete unravelling fails to occur in all our treatments. Receiver's beliefs and guesses about non-disclosed information are similar across the Consultation and Context treatments relative to the Baseline implying that naivety about hidden information is a robust phenomenon. We also find that senders are partly to blame for the lack of unravelling, as intermediate types would gain from disclosing more often given the observed receiver behaviour.
Keywords: B49; C91; C92; D80; 330; Consultation; Context; Laboratory Experiment; Verifiable Information Disclosure